Performance Analysis of Wireless Optical Communication Systems - Awad, Shuhad Rabah; Unverdi, N. Ozlem (IEEE, 2025)
In this study, a Free Space Optical (FSO) communication system and an Optical Wireless Communication (OWC) system were analyzed under different conditions. The systems were examined using fundamental parameters such as attenuation, modulation, and the maximum quality factor. These systems were modeled using the OptiSystem 18 simulation program, and their performances were evaluated under various weather and water conditions.
Keywords: Communication technologies; Free Space Optical (FSO) communication; Optical Wireless Communication (OWC); modulation; maximum quality factor; Computer Science; Engineering; Telecommunications